SOSIALISASI KEAMANAN PANGAN SERTA PELATIHAN MANAJEMEN KEUANGAN BAGI UMKM PANGAN MILIK WARGA ‘AISYIYAH KAB SUKOHARJO - Handriani, Eka; Abidin, Zaenal; Listyowati, Listyowati (Tahta Media Grup, 2025)
The purpose of this community service is to increase the knowledge, awareness, and skills of food MSMEs owned by Aisyiyah residents in Sukoharjo Regency regarding the importance of food safety and business financial management. Through this outreach and training activity, it is hoped that MSMEs will be able to apply food safety principles in the production process and manage business finances in a more orderly, effective, and sustainable manner. This community service was carried out in the Sukoharjo Regency area, involving Aisyiyah residents as the main participants. Participants consisted of food MSMEs who are members of the Aisyiyah organization in Sukoharjo Regency. The methods used in this community service included lectures, discussions, and interactive Q&A sessions related to food safety and MSME financial management. This activity also encouraged the emergence of collaborative initiatives among MSMEs to improve product quality and business sustainability. The obstacles faced in implementing this activity were that some MSMEs still had limited initial understanding of food safety standards and business financial records.